2016
DOI: 10.1080/13200968.2016.1196532
|View full text |Cite
|
Sign up to set email alerts
|

Whose Reparation Claims Count? Gender, History and (In)justice

Abstract: The recognition and compensation of historic injustices is part and parcel of a politics of recognition and of socio-legal attempts of reconciliation and redemption.The notion of 'restorative justice' has recently gained political salience by invoking national governments to face and deal with historical injustice and often judicial recourse is used as a means to redress, through legislation, the legacy of historical wrongs in which democratic nation states have been implicated. At least, it would appear so wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The Swedish medical profession was split on the acceptability of eugenic sterilisations [10,27]. Public opinion was alerted to the issue when the Swedish newspaper Dagens Nyheter, in 1997, and Maija Runcis, in her doctoral thesis, in 1999, revealed that thousands of Swedes had been involuntarily sterilised [28]. In response to the media frenzy this caused, with a ripple effect in other countries, the Swedish Government set up a Commission to investigate this matter.…”
Section: Swedenmentioning
confidence: 99%
“…The Swedish medical profession was split on the acceptability of eugenic sterilisations [10,27]. Public opinion was alerted to the issue when the Swedish newspaper Dagens Nyheter, in 1997, and Maija Runcis, in her doctoral thesis, in 1999, revealed that thousands of Swedes had been involuntarily sterilised [28]. In response to the media frenzy this caused, with a ripple effect in other countries, the Swedish Government set up a Commission to investigate this matter.…”
Section: Swedenmentioning
confidence: 99%
“…Certain courts ordered that damages be paid. Later, there were moves to right historic injustices by means of recognition, acknowledgement, apologies and/or financial redress [3]. Reparations for sterilisations done before 1945 were generally made much later; some after 1997.…”
Section: From Theory To Interventionmentioning
confidence: 99%
“…These apologies were accepted as accountability for past eugenic policies and measures. So far, only in North Carolina (2013) and Virginia (2015) was redress in the form of financial compensation offered [3]. North Carolina has a US$10 million fund for payments but, to qualify, individuals must have lodged an application with the State Eugenics Board (later amended to include county authorisation).…”
Section: Accountability For Past Eugenic Policiesmentioning
confidence: 99%
“…Although loss of the ability to bear children generally cannot be reversed (usually unfeasible in low-resource countries or many years after the event), it has become apparent that reparations not only give people restorative justice but in a small way also some peace of mind 12. However, it may be many years before admission that the injustices actually occurred is forthcoming, let alone giving survivors any redress.…”
Section: Historical Contextmentioning
confidence: 99%